Decidualized Endometriosis Causing Inversion of the Appendix, Massive Hemorrhage and Fetal Death - Anthony M Magliocco; Robert Mulloy; Roy M Preshaw; James K Kelly (Canadian Journal of Gastroenterology)
An extraordinary case of inversion of the appendix due to decidualized endometriosis is reported. A 35-year-old woman presented at 3 7 weeks of pregnancy with acute massive rectal hemorrhage and fetal death. A limited right hemicolectomy was performed. The cecum contained an inverted appendix with an ulcerated tip. Histologically there was decidualized endometriosis in the ulcer bed and in all layers of the appendiceal wall.